PK/PD modeling links accelerated resolution of COVID‐19‐related clinical symptoms to SARS‐CoV‐2 viral load reduction in patients following treatment with Bamlanivimab alone or Bamlanivimab and Etesevimab together - C. Steven Ernest II; Jenny Y. Chien; Dipak R. Patel; Emmanuel Chigutsa (Wiley, 2022)
Abstract The relationship between severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) viral load reduction and disease symptom resolution remains largely undefined for coronavirus disease 2019 (COVID‐19). While the vaccine‐derived immunity takes time to develop, neutralizing monoclonal antibodies offer immediate, passive immunity to patients with COVID‐19. Bamlanivimab and etesevimab are two potent neutralizing monoclonal antibodies directed to the receptor binding domain of the spike protein of SARS‐CoV‐2. This study aims to describe the relationship between viral load and resolution of eight common COVID‐19‐related symptoms in patients following treatment with neutralizing monoclonal antibodies (bamlanivimab alone or bamlanivimab and etesevimab together), in a phase II clinical trial. Corresponding pharmacokinetics (PKs), viral load, and COVID‐19‐related symptom data were modeled using Nonlinear Mixed Effects Modeling to describe the time‐course of eight COVID‐19‐related symptoms in an ordered categorical manner (none, mild, moderate, and severe), following administration of bamlanivimab or bamlanivimab and etesevimab together to participants with COVID‐19. The PK/pharmacodynamic (PD) models characterized the exposure‐viral load‐symptom time course of the eight preselected COVID‐19‐related symptoms. Baseline viral load (BVL), change in viral load from baseline, and time since the onset of symptoms, demonstrated statistically significant effects on symptom score probabilities. Higher BVL generally indicated an increased probability of symptom severity. The severity of symptoms decreased over time, partially driven by the decrease in viral load. The effect of increasing time resulting in decreased severity of symptoms was over and above the effect of decreasing viral load. Administration of bamlanivimab alone or together with etesevimab results in a faster time to resolution of COVID‐19‐related symptoms compared to placebo.